Pengaruh Media Sedotan Plastik Terhadap Keterampilan Guling Depan Siswa Kelas V MI Islamiyah Tulungagung - Saputra, Aldy Wahyu; Cahyani, Olivia Dwi; Da'i, Mohamad (Universitas Hamzanwadi, 2026)
The main difficulty in learning forward rolls in elementary school gymnastics often lies in incorrect head and neck positioning, which prevents rotation and increases the risk of injury. This study aims to examine the effect of using plastic straws as a learning aid to improve students' forward roll skills. The method used is a quasi-experiment (pre-experiment) with a one-group pretest-posttest design. The research subjects were 30 fifth-grade students at MI Islamiyah Tulungagung who were given treatment during six meetings with the help of plastic straws placed between the chin and chest as an indicator of head position. Skill data were assessed through an observation test covering initial attitude, process, and final attitude aspects, then analyzed using a paired sample t-test and Cohen's d effect size calculation. The results showed an average skill improvement from 60.13 (pretest) to 70.83 (posttest), with a significant difference (p = 0.001). The effect size was categorized as moderate (d = 0.65). Based on these findings, it can be concluded that plastic straws are effective and have a significant influence in improving students' forward roll skills, particularly through improving head position during rotation. This medium is recommended as a simple, inexpensive, and direct feedback-based learning alternative for physical education teachers in elementary schools.